Nothing but the dirt stories from an American farm town - Benz, Kate Guerriero (University Press of Kansas, 2022)
"In this work of creative nonfiction, Kate Benz provides an intimate look at the present-day residents of Courtland, Kansas (population 285), a town whose economy depends almost entirely on agriculture. Her narrative shows how macro-level issues, from rising tariffs and operation costs to sinking commodity prices and infusions of federal farm subsidies affect these Americans' daily lives, and how their love of their community continues their collective efforts to keep Main Street open for business and Courtland on the map"--